Konsep Istiqra dalam Penetapan Hukum Islam: The Concept of Istiqra in Determining Islamic Law - Amiruddin Aminullah (Dirasat Islamiah: Jurnal Kajian Keislaman, 2024)
Muslims have two absolute sources of law, namely the Qur'an and the Hadith. In deciding the law of a case, it is necessary to utilize the collectivity of evidence from various forms, both those related to the text directly (manqulah) or indirectly (ghairu manqulah). The use of the collectivity of evidence to decide a case in the discussion of ushul fiqh is called istiqra. This istiqra method was developed by the Maliki scholar, namely Imam Al-Syatibi, who is more popularly known as istiqra al-ma'nawi. Istiqra means inductive and al-ma'nawi means integralistic. What is described about this method is at least an interesting offer when understanding legal texts. Because this is different from the methodological formulation that has been offered by previous schools of thought which are deductive of concrete regulations from texts. In the “istiqra” approach, all the evidence on the same theme in the Qur'an and al-Sunnah, even from the interpretations of the companions, tabi'in, hadith commentary, tafsir books, are taken as collective references, then arranged to draw substantive legal conclusions.